Conversion of algal biomass into renewable fuel: A mini review of chemical and biochemical processes - Rony, Zahidul Islam; Mofijur, M.; Hasan, M. M.; Ahmed, Shams Forruque; Badruddin, Irfan Anjum; Khan, T. M. Yunus (Frontiers in Energy Research, 2023)
Microalgae are a vital resource for the coming years to address the concern of decrease in oil reserves and the negative impacts of fossil fuels on the environment. Their utilization is crucial for a wide range of industrial applications. Depending on the strain, microalgae contain a variety of chemical components and can be treated biochemically or thermochemically. This review thus focuses on the biochemical mechanisms that are used to convert algal biomass into sustainable fuel, including the challenges and potential of those processes. Microalgae have been shown to be a viable third-generation alternative to conventional biofuel feedstocks. The optimum production of biofuel depends on the proper selection of microalgae species based on their lipid, carbohydrate, and protein content in order to produce high-quality, sustainable biofuel. Nannochloropsis gaditana can contribute to a maximum biodiesel yield of 96.47%, whereas Nannochloropsis oculata can produce the least (25%) through the biochemical process of transesterification. Higher yields of microalgae-derived gaseous, solid and liquid fuels can be achieved by pre-treating microalgal biomass and then employing bioconversion processes such as photo-fermentation and hydrothermal carbonization.